Real Wage Growth in Papua New Guinea Over Three Decades - Niels‐Hugo Blunch; Martin Davies (Asia & the Pacific Policy Studies)
ABSTRACT As a key determinant of household welfare, workersʼ real wages matter. Limited by small and infrequent surveys, the study of real wages in Papua New Guinea (PNG) has until now been constrained by a paucity of data. Using a novel dataset, we construct the first longitudinal series of wages for (to a close approximation) the population of formal private sector workers in PNG over a 3 decades span from 1999 to 2018. We examine real wage growth for the formal private sector in PNG over a 20‐year period using panel regression. Among the main findings are that conditional real wage growth has averaged about 4.5%. Also, real wage developments closely mirror the bust‐boom‐bust episodes of the macroeconomic cycle. Further, conditional real wage growth in the agricultural sector lagged that in services, industry, and mining with agriculture hardest hit during busts and lagging during the boom and mining the winner. Men experience higher conditional real wage growth during booms but also bear the majority of the decrease during busts. Finally, we establish the strong co‐movement of the real exchange rate (RER) and the conditional real wage, providing support for the RER as an important determinant of real wages in PNG.